Strategi Guru dalam Mengadopsi Artificial Intelligence untuk Pengembangan Pembelajaran di SMP - Anindya Rosalina; Eva Dianawati Wasliman; Sri Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was conducted using a descriptive qualitative approach. The researcher took a sample of research subjects, namely teachers at SMP Negeri 38 Bandung who had used AI in learning. Research data were obtained through the distribution of Google Form instruments, in-depth interviews, and documentation studies. Data analysis was performed using thematic analysis techniques. The conclusions of this study are: 1) teachers' AI adoption strategies, including stages ranging from planning, implementation, and evaluation, as well as supporting components and obstacles in the AI adoption process at SMP Negeri 38 Bandung, encompass several principles and stages of classical management theory according to Fayol, Terry, and Deming; 2) The AI used by teachers is in the form of web-based AI applications such as ChatGPT, Quizizz, Canva AI, and others; 3) Factors supporting AI adoption by teachers include environmental factors (internet access and support from colleagues), while the inhibiting factors are teacher competence (digital competence, devices, and training/formal education); 4) Teachers overcome obstacles by learning independently, collaborating, and implementing rules for AI use; and 5) The impact of AI adoption includes increased student motivation and learning outcomes as well as creativity in learning methods. It is hoped that this research will contribute relevant insights to the development of policies on teacher competency development, particularly in the field of teaching.